Adverse Effects of Genetically Modified Products on Human Health (Review Article) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Most of the food consumed is either completely genetically modified food, or a type of food that includes food components produced using genetic modification technology. Among the doubts about GMOs that are widely used and consumed around the world, the most pressing issue is the likely health risks caused by eating GMOs. As uncertainty about GM products persists, studies conducted in many countries have shown that there are many differences in gene transfer. some features that cause allergies and diseases can be transmitted from another organism, and as a result, there may be a risk of detecting unexpected biochemical products in transgenic products. information, attitudes and behavior of people to this issue in different countries.